THE CULT OF SAINT GEORGE IN THE MICROTOPONYMY OF WESTERN MACEDONIA (Slavic Studies, 2025)
The text deals with the origin of several toponyms in Western Macedonia, based on field data indicating that certain ritual practices for the spring celebration of Saint George are associated with the toponyms. Tracing the beliefs and practices of Gjurgjovden allows for a deeper interpretation of the toponymic material, with the naming of these places rooted in the Christian saint George and his non-Christian, Slavic counterparts.
Keywords: toponymy; Slavic mythology; Jaroshtica/Jarojca, Gjurgjejca, Markoec